Isoflurane post-conditioning influences myocardial infarct healing in rats. (4th July 2018) - Agnic, I; Filipovic, N; Vukojevic, K; Saraga-Babic, M; Grkovic, I
Abstract: Isoflurane post-conditioning causes an early increase in cardiac progenitor cells; however, during the chronic phase of infarct healing, the number was smaller compared to control, which suggests a positive effect on infarct scar maturity. Myofibroblasts participate in early phase infarct contraction, but their number is small in a mature scar. We investigated whether isoflurane post-conditioning stimulates differentiation of progenitor cells to myofibroblasts and to verify our hypothesis that isoflurane post-conditioning improves maturation of a myocardial scar. Ischemia was induced for 30 min in female rats. From the last 5 min of ischemia until 10 min into reperfusion, the isoflurane group received 1.5% isoflurane, while the control group received only an air-oxygen mixture. Infarct area was analyzed using immunohistochemistry. During the subacute phase of infarct healing, the number of myofibroblasts was greater in isoflurane-treated animals than in the control group. During the chronic phase of infarct healing, post-conditioned animals exhibited fewer myofibroblasts compared to control animals, even those derived from progenitor cells, i.e., α-smooth actin-nestin positive cells. In addition, isoflurane post-conditioning resulted in higher percentage of mature blood vessels compared to control animals. The myocardium of the isoflurane treated animals exhibited more myofibroblasts in granulation tissue compared to control animals. The smaller number of myofibroblasts together with the greater number of mature blood vessels during the chronic phase of healing demonstrated faster healing of the infarct area of isoflurane-treated animals compared to control animals.